2014
DOI: 10.1016/j.niox.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of recent exposure to ambient metals on fractional exhaled nitric oxide in 9–11year old inner-city children

Abstract: Exposure to ambient metals in urban environments has been associated with wheeze, and emergency room visits and hospitalizations due to respiratory illness. However, the effect of ambient metals exposure on airway inflammation, and how these associations may be modified by seroatopy, has not been determined. Fractional exhaled nitric oxide (FENO) is a reliable proxy marker of airway inflammation. We hypothesized that recent ambient concentrations of Ni, V, Zn and Fe would be associated differentially with prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…We observed enhanced FeNO with exposure to PM 2.5 characterized by increased glutathione-related oxidative burden for children with allergies to mold, fur, or dust. Suggestions of enhanced exacerbations of asthmatic symptoms in children exposed to traffic-related pollutants and allergens have been reported previously for exposures to nitrogen dioxide ( Dell et al 2014 ), black carbon ( Cornell et al 2012 ), formaldehyde and acetaldehyde ( Flamant-Hulin et al 2009 ), as well as trace metals (nickel from residential oil heating) ( Rosa et al 2014 ). Ours is the first report to show that the effects of pro-oxidant exposure, quantified by oxidative burden, may be modified by the presence of allergic disease, although we must emphasize that there was no clear signal in these interaction analyses.…”
Section: Discussionmentioning
confidence: 85%
“…We observed enhanced FeNO with exposure to PM 2.5 characterized by increased glutathione-related oxidative burden for children with allergies to mold, fur, or dust. Suggestions of enhanced exacerbations of asthmatic symptoms in children exposed to traffic-related pollutants and allergens have been reported previously for exposures to nitrogen dioxide ( Dell et al 2014 ), black carbon ( Cornell et al 2012 ), formaldehyde and acetaldehyde ( Flamant-Hulin et al 2009 ), as well as trace metals (nickel from residential oil heating) ( Rosa et al 2014 ). Ours is the first report to show that the effects of pro-oxidant exposure, quantified by oxidative burden, may be modified by the presence of allergic disease, although we must emphasize that there was no clear signal in these interaction analyses.…”
Section: Discussionmentioning
confidence: 85%
“…Cohort studies have suggested that acute (e.g., same day) and subacute (e.g., cumulative over days to one week) exposures to BC may exacerbate respiratory symptoms and increase airway inflammation among urban children [ 2 4 ]. Others have identified short-term lag effects (e.g., up to 5 days) of measures of air pollution on airway-related outcomes [ 2 , 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Seattle, ambient particulate matter less than 2.5 μ m in diameter (PM 2.5 ) was found to be associated with exhaled NO in children with and without asthma [ 14 ]. A study conducted in healthy children aged 9–11 years in New York found a relationship between exposure to ambient metals and increased FeNO [ 4 ]. Another study performed at 25 schools in the Netherlands found a positive association between ambient PM 10 concentrations on the day exhaled NO was measured [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…e ., particulate matter, ambient NO, and carbon monoxide) or occupational exposure ( i . e ., organic solvents and heavy metals) [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation